1991
DOI: 10.4319/lo.1991.36.7.1358
|View full text |Cite
|
Sign up to set email alerts
|

Diagenesis of belowground biomass of Spartina alterniflora in salt‐marsh sediments

Abstract: Belowground biomass of Spartina alterniflora lost 55% of its organic matter during 18 months of decomposition in salt-marsh sediments. Significant losses of lignin were observed under highly reducing conditions confirming previous reports of lignin degradation in the absence of molecular oxygen. The submolecular components of lignin varied in susceptibility to degradation and were ranked in the following descending order of resistance to decomposition: V-P> S-C. The preferential degradation of 1 he cinnamyl an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
103
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 218 publications
(113 citation statements)
references
References 32 publications
6
103
1
Order By: Relevance
“…The oldest sediments have had the most time for mineralization processes to occur. N concentrations decreased more rapidly with depth than did C, which suggests preferential remineralization of N rich compounds (Benner 1991;Hopkinson and others 1997). P sediment depth profiles were more variable, showing no broad down core trends.…”
Section: Terrestrial Biomass Drives Sediment Accumulationmentioning
confidence: 88%
“…The oldest sediments have had the most time for mineralization processes to occur. N concentrations decreased more rapidly with depth than did C, which suggests preferential remineralization of N rich compounds (Benner 1991;Hopkinson and others 1997). P sediment depth profiles were more variable, showing no broad down core trends.…”
Section: Terrestrial Biomass Drives Sediment Accumulationmentioning
confidence: 88%
“…Mellilo et al (1989) showed a non-linear pattern in a 77-month period, with 15 N depletion during the initial 22 months and slight 15 N enrichment during the remainder of 55 months. Benner et al (1991) reported that significant 15 N depletion occurred during a period of 18 months. Connin et al (2001) did not show a clear pattern for 15 N dynamics during litter decomposition over 6 years.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have suggested that 15 N enrichment occurred in the remaining litter with decomposition time (Nadelhoffer and Fry 1988;Asada et al 2005). However, a non-linear pattern was observed in a red pine plantation during a 77-month period (Mellilo et al 1989) while significant 15 N depletion was found during 18 months of decomposition of belowground parts in salt-marsh sediments (Benner et al 1991). Over a period of 6 years, there was no clear pattern for 15 N dynamics during litter decomposition (Connin et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the plant material, Morrisson (1989) verified, after temporal measurements, that litter had a lower C:N ratio due to heterotrophic bacteria colonization. On the other hand, Benner et al (1997) found that the N content in decomposing Spartina tissues was highly variable, which was reflected in the wide range of C:N values, and that a major fraction (>50%) of the initial N in the tissue was lost during the early stages of decomposition, followed by the slow accumulation of exogenous N. No significant differences were found concerning the sediment C:N and N:P ratios during the degradation period. It has been shown that bacteria grow very rapidly in shallow water estuaries where efflux from the sediment dominates the dynamics in the water column (Hopkinson et al, 1998).…”
Section: Discussionmentioning
confidence: 81%
“…In fact, it has been shown for other plant species that, in undisturbed marsh sediments, the major fate of below-ground production appears to be microbial decomposition (Benner et al, 1997), although the presence of meiofauna may also enhance the degradation (e.g. DeMesel et al, 2004).…”
Section: Discussionmentioning
confidence: 99%